Algorithm for Object Collection Using a Robotic Manipulator and Machine Vision - Martinez Baquero, Javier Eduardo; Jimenez Moreno, Robinson; Garcia Veloza, David (LACCEI, 2024)
This document presents the detection of paper waste and its collection through a robotic agent in a mixed real-virtual validation system. An interface is designed in which the image of the robot's workspace is input, and the presence and location of paper waste are detected. For this purpose, a three-degree-of-freedom anthropomorphic robotic arm is implemented, and by calculating its kinematics, it moves to the waste location and collects it.